2021
DOI: 10.1111/hiv.13180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coronavirus disease (COVID‐19) on HIV testing and care provision across four continents

Abstract: Objectives The coronavirus disease (COVID‐19) pandemic has been associated with severe disruptions in health care services, and nonpharmacological measures such as social distancing also have an impact on access to screening tests and on the long‐term care of patients with chronic conditions globally. We aimed to describe the impact of the COVID‐19 pandemic on HIV testing and treatment and to describe strategies employed to mitigate the impact of COVID‐19 on HIV care. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 20 publications
4
59
1
1
Order By: Relevance
“…Our data are consistent with other reports demonstrating the negative impact of the pandemic on HIV testing globally. In a recent report from 44 high HIV burden countries across Africa, Latin America, the Caribbean, Asia and Europe, a reduction of HIV testing was observed across nearly all sites ranging from 26% to 44% [14]. While there was heterogeneity across sites, the same study observed an increase in test positivity ranging from 2% to 44%.…”
Section: Discussionmentioning
confidence: 92%
“…Our data are consistent with other reports demonstrating the negative impact of the pandemic on HIV testing globally. In a recent report from 44 high HIV burden countries across Africa, Latin America, the Caribbean, Asia and Europe, a reduction of HIV testing was observed across nearly all sites ranging from 26% to 44% [14]. While there was heterogeneity across sites, the same study observed an increase in test positivity ranging from 2% to 44%.…”
Section: Discussionmentioning
confidence: 92%
“…Data from the AIDS Healthcare Foundation (AHF) Global Quality Program from 44 countries demonstrated a significant reduction in the number of HIV tests, ranging from 26.19% in Europe to 44.62% in Latin America, and 35.4% in the Caribbean, between January and August 2020, compared with the equivalent time period in 2019. 9 An interrupted time series analysis of a large dataset from 65 South Africa primary care clinics between January 1, 2018 and July 31, 2020 showed a 47.6% decrease in HIV testing in April 2020. 16 In a recent report from The Joint United Nations Programme on HIV/AIDS (UNAIDS) also showed a reduction in HIV testing in 16 out of 19 countries, and a decline in initiation of antiretroviral therapy (ART) in 28 out of 29 countries.…”
Section: Discussionmentioning
confidence: 99%
“… 8 COVID-19 control measures such as lockdowns, ED priorities, and/or social distancing were vital for containing the spread of the COVID-19 pandemic, but might have had severe collateral effects on existing health care services, like ED-based HIV screening programs. 9 The COVID-19 pandemic across the U.S. with extensive publicity and lockdowns began in mid-March 2020. Herein, we report the results of ED-based opt-out HIV tests between July 2018 and March 2021 at MHS.…”
Section: Introductionmentioning
confidence: 99%
“…While health services have general remained open during these periods, health system pressures associated with COVID‐19 1 and community concerns about attending health services and COVID‐19 acquisition risk 2 , 3 , 4 have challenged the maintenance of routine health service delivery. Of great concern is the impact of the pandemic and subsequent government‐imposed restrictions on access to healthcare, 5 , 6 including testing and treatment for other communicable diseases. Global disease elimination strategies, which necessitate high rates of testing and treatment among priority populations such as those for the elimination of hepatitis B and hepatitis C, are likely to be hindered by widespread reductions in access to healthcare during the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%